Vortex coagulation treatment of oilfield wastewater. (25th November 2022) - Wu, Lulu; Wang, Yifei; Zhang, Naidong
Abstract: In this study, the traditional coagulation process was optimized and a method of vortex coagulation for wastewater treatment was proposed for the first time. The process discards the sedimentation method used in traditional coagulation and uses agitation to bring flocs up. These flocs can then be stuck by the filter cotton fixed in wastewater, and the filter cotton and flocs can act as net capturing several times under the action of agitation. It is worth noting that the filter cotton and flocs can synergistically adsorb the suspended and organic pollutants from wastewater. The results showed that the chemical oxygen demand (COD) removal of vortex coagulation could reach 82%, which was 10% higher than that of the traditional coagulation under the same coagulant dosing. In addition, the flocs in conventional coagulation and vortex coagulation were analyzed by IR spectroscopy and XRD, which showed that the mixing process did not destroy the chemical structure of the flocs. Compared with the conventional method, this process does not require a sedimentation tank, which can avoid the investment of equipment construction in this area. The effects of coagulant dosage, pH, stirring speed, and stirring time on the wastewater treatment effects were explored in the experiment. HIGHLIGHTS: Compared with the traditional coagulation process, this method has better treatment effect. This method does not require equipment such as sedimentation tanks, which can save costs. This method can simplify and shorten the process of combining with adsorption method. Graphical Abstract